1989
DOI: 10.1177/004051758905900506
|View full text |Cite
|
Sign up to set email alerts
|

Theory of the Shear Deformation of Fibrous Assemblies

Abstract: The initial response of the unit fibrous cell to an externally applied shear stress is assumed to involve both the bending of fiber sections and slippage at contact points. The criterion used to determine whether a contacting fiber will bend the contacted fiber section or whether it will slip along it depends on the relative angles of the two fiber sections to the external stresses. The total proportion of slipping and nonslipping contact points is thus derived using the density function of fiber orientations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 9 publications
1
31
0
Order By: Relevance
“…However, Grosberg and Smith 34,91 have shown that if one pulls a fiber from a twistless sliver, the withdrawal force WF per unit length of fiber required is given by WF ϭ ЈP ϩ WFo (17) where P is the external pressure applied to the fiber mass; Ј is the equivalent frictional coefficient but with dimensions of length, and WFo is the value for WF when P ϭ 0, that is, the cohesion force. This conclusion has been utilized by Carnaby and Pan 75,86 to predict the compressional hysteresis and the shear modulus of fiber assemblies.…”
Section: The Coulomb Yield Criterion and The Fiber Pullout Forcementioning
confidence: 99%
See 1 more Smart Citation
“…However, Grosberg and Smith 34,91 have shown that if one pulls a fiber from a twistless sliver, the withdrawal force WF per unit length of fiber required is given by WF ϭ ЈP ϩ WFo (17) where P is the external pressure applied to the fiber mass; Ј is the equivalent frictional coefficient but with dimensions of length, and WFo is the value for WF when P ϭ 0, that is, the cohesion force. This conclusion has been utilized by Carnaby and Pan 75,86 to predict the compressional hysteresis and the shear modulus of fiber assemblies.…”
Section: The Coulomb Yield Criterion and The Fiber Pullout Forcementioning
confidence: 99%
“…On the other hand, the existing fiber contact point will also abate the free volume of the fiber mass, and consequently increase the chance for successive fibers to make new contacts. Some of the research results in this area have been applied to study the compressional 75,83 and shear 86 behavior of general fiber assemblies, as well as the prediction of nonwoven products, 77 leading to considerable progress in those areas.…”
Section: Fiber Packing Problemmentioning
confidence: 99%
“…By denoting a and b as the semi-axes of the ellipse of the contact zone, the peak pressure can be determined by (11) from which we have (12) In the above P is the compressive force that is actually the resultant adhesive force between two filaments in contact. The peak pressure is 1.5 times the average pressure on the contact surface, and a is related to the compressive force P and the semi-axes of the ellipse a and b [29] such that (13) where the semi-axes a and b are determined as (14) In the above, coefficients m and n are numbers depending only on the ratio (B -A) to (A + B) as tabulated in the literature [28]. Now, let us consider the compressive force induced by surface adhesion between filaments in contact.…”
Section: Problem Statement and Solutionmentioning
confidence: 99%
“…Figure 2 Contacting illustration between the tension disk and the yarn. where is the effective aspect ratio of the fiber within the contacting area of the tension disk, and n c1 is the mean number of fiber contacts over the length L e1 , and other parameters can be obtained from Hickie and Chaikin [3] and Pan [6]. The fiber length L e2 , which is outside the acting area of the tension disk, can be calculated as:…”
Section: Analysis Of a Protruding Fiber End In The Tension Diskmentioning
confidence: 99%